2013
DOI: 10.1093/ndt/gft251
|View full text |Cite
|
Sign up to set email alerts
|

Ferric carboxymaltose in patients with iron-deficiency anemia and impaired renal function: the REPAIR-IDA trial

Abstract: Two 750-mg infusions of FCM are a safe and effective alternative to multiple lower dose iron sucrose infusions in NDD-CKD patients with iron-deficiency anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
92
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 19 publications
5
92
0
4
Order By: Relevance
“…The study demonstrated that ferric carboxymaltose was safe, effective and required fewer doses making it potentially more cost-effective than iron sucrose. 19 Other studies have also found favourable cost-effectiveness. 20 One limitation is ferric carboxymaltose can only be infused in doses up to 1 g per week.…”
Section: Articlementioning
confidence: 98%
See 1 more Smart Citation
“…The study demonstrated that ferric carboxymaltose was safe, effective and required fewer doses making it potentially more cost-effective than iron sucrose. 19 Other studies have also found favourable cost-effectiveness. 20 One limitation is ferric carboxymaltose can only be infused in doses up to 1 g per week.…”
Section: Articlementioning
confidence: 98%
“…Full text free online at nps.org.au/australianprescriber VOLUME 39 : NUMBER 6 : DECEMBER 2016 REPAIR-IDA 19 reported a higher incidence of mild adverse events in patients treated with ferric carboxymaltose compared to iron sucrose. These included mild hypersensitivity reactions, nausea and flushing, however there was no statistically significant difference on the pre-specified safety end points.…”
Section: Articlementioning
confidence: 99%
“…Anemia in CKD patients may be caused by iron deficiency, inflammation, or a disruption in the production of erythropoietin (EPO) [2,3]. Erythropoietin is a hormone that stimulates the production of red blood cells [4]. Deficiencies of this hormone are currently managed with erythropoietin stimulating agents [ESAs], usually in combination with iron supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…An important function of the kidneys is the production of erythropoietin, a hormone that stimulates production of red blood cells [1][2][3]. The kidneys produce this hormone in response to oxygen tension and extracellular volume [3].…”
Section: Introductionmentioning
confidence: 99%
“…The kidneys produce this hormone in response to oxygen tension and extracellular volume [3]. In disease states such as Chronic Kidney Disease (CKD) the kidneys are not functioning at capacity and there can be a disruption in the production of erythropoietin that can lead to anemia [1,2]. Other causes of anemia in CKD are iron deficiency and inflammation.…”
Section: Introductionmentioning
confidence: 99%